A Linguistic Investigation of the Body’s Parts in the Holy Quran - Hazaymeh, Hamzeh Mohammad Ameen (MultiTech Publisher, 2024)
The Holy Quran talked about the creation of man and mentioned in many of its verses a bulk number of the internal and external parts of the human body, which were used in multiple linguistic formulas. The present research aims to study some of these parts from a linguistic point of view, where the present study has investigated the linguistic structure and forms of these parts, their numbers, and the suras and verses in which they are used. The main source of the required data is the Holy Quran. Related studies were of great help for this study. The corpus of the study is limited to a number of these parts that were found to be the most used ones in the Holy Quran which were investigated deeply and thoroughly. The findings show that the targeted parts were formed in the Arabic singular, dual and plural forms. It also shows that some of these parts were used more than others. The study also concluded that the great majority of the linguistic forms of these parts were used for both men and women with a very limited exceptions where some of these linguistic forms were only used for women.